Comparison of continuous infusion versus repeated bolus of Pralidoxime for the treatment of Organophosphosphate Pesticide poisoning - Mandeep Kaur; Balwinder Kaur; Shivani; Arshdeep Singh (GMC Patiala Journal of Research and Medical Education, 2019)
Background The present study compared the continuous infusion versus repeated bolus dose of pralidoxime for the management of organophosphate pesticide poisoning in terms of death(%), recovery (%), sequelae(%), mean atropine dose in 24hrs, mean ventilator days, total ICU stay, total hospital days, pneumonia, intermediate syndrome and its complications. Material and Methods This was a randomized control study. Carried out on 64 patients of either sex 15-65 years who presented in emergency medicine ward at Rajindra Hospital, Patiala. The patients who gave consent for the trial were given 2 gm of loading dose of pralidoxime over 30 mins and then randomized into two groups by simple random method:- Group I (n=32)– After loading dose, patients were given continuous infusion of pralidoxime 1gram/ hour for 48 hours. Group II (n=32) – After loading dose, patients were given repeated bolus dose of pralidoxime 1 gram/ hour every 4hourly for 48 hours.Thereafter, pralidoxime was continued at a rate of 1 gram/ hour every 4hourly till the patient was on ventilatory support. Result The mean atropine dose in group I was 32.7812± 7.17853 and in group II was 41.2812 ± 10.02974. The difference between them was statistically highly significant (p value <0.001). The mean ventilation days in group I was 5.2222 ± 2.97856 and in group II was 7.7037± 4.89753. The difference between them was statistically significant. (p value is 0.029). The mean hospital days in group I was 8.2188± 3.73937and in group II was 11.0938 ± 6.41248. The difference between them was statistically significant. (p value is 0.032). Conclusion With this study we concluded that, the infusion dose of pralidoxime was better than repeated bolus dose of pralidoxime in terms of mean atropine dose required mean ventilator days and total hospital stay.